The use of geographical information systems for tourism marketing purposes in Aveiro region (Portugal) - Albuquerque, Helena (2019)
Geographical Information Systems are tools that allow a better decision making process, accessing politicians and managers in tourism development and providing integrated touristic information. Furthermore, these are powerful tools for the development of destination marketing strategies. Aveiro web-based Geographical Information System was developed, with the purpose of integrating tourism resources in a common platform. Aveiro region is an important coastal wetland of Portugal that presents unique features which allow the development of a sustainable tourism activity, based on natural and cultural characteristics. Despite the diversified resources, it is observed that the Aveiro region needs a strong improvement regarding tourism development and marketing strategies. In this paper, it will be presented the methodology used for the implementation of the first step of this GIS (inventory of resources and creation of the database) and the potential of this tool for the development of a sustainable tourism marketing strategy.